2001
DOI: 10.1007/s101510170005
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised study of drains in infra-peritoneal rectal anastomoses

Abstract: group with a clinical leak. There were no specific drain complications and the incidence of other complications was similar in both groups. In conclusion, this study supports the contention that there is no difference in morbidity with or without the use of a drain for infra-peritoneal anastomoses.Abstract Although increasing evidence suggests that prophylactic drainage after intra-peritoneal colorectal anastomoses is unnecessary, drains for infra-peritoneal rectal anastomoses, where the leak rate is higher, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 13 publications
1
59
0
10
Order By: Relevance
“…Six further studies were identified through hand searching of references. After the evaluation of full-texts, 4 studies [12, 13, 19, 20] eventually met all the inclusion criteria and were included in the meta-analysis. The flow diagram in Figure 1 describes the selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six further studies were identified through hand searching of references. After the evaluation of full-texts, 4 studies [12, 13, 19, 20] eventually met all the inclusion criteria and were included in the meta-analysis. The flow diagram in Figure 1 describes the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Three [12, 13, 20] of the included studies were from Europe and one from Asia [19]. Three studies included only patients with extraperitoneal anastomoses [12, 13, 19], whereas the other RCT [20] referred to any type of anastomosis following rectal surgery but provided specific data concerning the group of patients with extraperitoneal anastomosis (132 patients out of 494).…”
Section: Resultsmentioning
confidence: 99%
“…Six of eight RCTs had included specific population of patients based on the level of the anastomoses [12,[34][35][36][37][38], whereas two RCTs were composed of a heterogeneous population [33,39] (Table 1). Two trials included only cancer patients [35,37]; in six trials, benign disease patients were also included. But these trials have predominantly cancer patients (61 to 77 %).…”
Section: Randomized Controlled Trailsmentioning
confidence: 99%
“…But these trials have predominantly cancer patients (61 to 77 %). Six trials [12,[33][34][35][36][37] studied only elective surgery, whereas two other also included emergency procedures [38,39]. However, emergency procedures were in the minority, and patients were equally represented in the drained and nondrained group in both studies.…”
Section: Randomized Controlled Trailsmentioning
confidence: 99%
See 1 more Smart Citation